2008
DOI: 10.1111/j.1439-0426.2008.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary l-carnitine supplements on growth and body composition in beluga sturgeon (Huso huso) juveniles

Abstract: The effects of dietary L L-carnitine on growth performance, whole body composition and feed utilization were studied in beluga, Huso huso. Fish were randomly allocated in 15 tanks (30 fish per tank) and triplicate groups were fed to satiety during 84 days one of five isonitrogenous (41% CP) and isoenergetic (20 MJ kg )1 ) diets, each differing in L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 23 publications
4
40
0
1
Order By: Relevance
“…This species is suitable for aquaculture because of its fast growth, easy reproduction and high tolerance to adverse environmental conditions [10]. Therefore, further identification of commercially available dietary additives to improve performance and disease resistance of these fish is still highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…This species is suitable for aquaculture because of its fast growth, easy reproduction and high tolerance to adverse environmental conditions [10]. Therefore, further identification of commercially available dietary additives to improve performance and disease resistance of these fish is still highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…The giant sturgeon (Huso huso) is the largest species of Acipenseriformes and one of the most important species of sturgeon in the Caspian Sea (Jalali et al 2008). This species is suitable for aquaculture because of its fast growth, ease of reproduction, and high tolerance to adverse environmental conditions (Mohseni et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that carnitine can reduce lipid content of muscle in sea bass (Santulli and D'Amelio, 1986b) and seabream (Sparus macrocephalus) (Ma et al, 2008). In addition, Mohseni et al (2008) showed that growth performance of sturgeon (Beluga beluga) was improved when fish was fed 300 mg L-carnitine kg -1 diet. Nevertheless, little or no effect of L-carnitine supplementation on growth was observed in other species (Burtle and Liu, 1994;Ji et al, 1996;Chatzifotis et al, 1997;Harpaz et al, 1999;Gaylord and Gatlin, 2000;Dzikowski et al, 2001;Ozório et al, 2001;Schlechtriem et al, 2004).…”
Section: Introductionmentioning
confidence: 99%